The Development of Self-Control Scale in Social Media - Febrianti, Indah Dwi; Febriyanti, Mariza Ningtyas; Adhania, Isna Rahma; Khasanah, Utari Nur; Andiny, Enno Arjuni Putri; Husna, Aftina Nurul (Prosiding University Research Colloquium, 2021)
The purpose of this study was to develop a psychological scale of self-control in social media. Self-control is the ability to control behavior and resist temptations that arise from within so as to be able to take action to avoid unwanted consequences, self-control has three aspects, namely the ability to control behavior, cognitive control and decision control. The stages of this research include confirming the measuring area by selecting the attribute of self-control, then making a blueprint for the self-control scale to limit the concept of self-control. Item writing refers to self-control indicators in social media, the content validity test involves 3 raters and the readability test involves 4 respondents according to the criteria. The data collection technique uses Convenien sampling, namely by uploading the "Social Media" questionnaire link on social media accounts. The reliability test on the self-control scale produces a Cronbach Alpha coefficient of 0.903, meaning that the reliability of the scale is very good. The final result of this scale consists of 20 items.